Molecular characterization of a Trichinella spiralis aspartic protease and its facilitation role in larval invasion of host intestinal epithelial cells. - Jia Xu; Ruo Dan Liu; Sheng Jie Bai; Hui Nan Hao; Wen Wen Yue; Yang Xiu Yue Xu; Shao Rong Long; Jing Cui; Zhong Quan Wang (Public Library of Science (PLoS), 2020)
Background T. spiralis aspartic protease has been identified in excretion/secretion (ES) proteins, but its roles in larval invasion are unclear. The aim of this study was to characterize T. spiralis aspartic protease-2 (TsASP2) and assess its roles in T. spiralis invasion into intestinal epithelial cells (IECs) using RNAi. Methodology/principal findings Recombinant TsASP2 (rTsASP2) was expressed and purified. The native TsASP2 of 43 kDa was recognized by anti-rTsASP2 serum in all worm stages except newborn larvae (NBL), and qPCR indicated that TsASP2 transcription was highest at the stage of intestinal infective larvae (IIL). IFA results confirmed that TsASP2 was located in the hindgut, midgut and muscle cells of muscle larvae (ML) and IIL and intrauterine embryos of the female adult worm (AW), but not in NBL. rTsASP2 cleaved several host proteins (human hemoglobin (Hb), mouse Hb, collagen and IgM). The proteolytic activity of rTsASP2 was host-specific, as it hydrolyzed mouse Hb more efficiently than human Hb. The enzymatic activity of rTsASP2 was significantly inhibited by pepstatin A. The expression levels of TsASP2 mRNA and protein were significantly suppressed by RNAi with 5 μM TsASP2-specific siRNA. Native aspartic protease activity in ML crude proteins was reduced to 54.82% after transfection with siRNA. Larval invasion of IECs was promoted by rTsASP2 and inhibited by anti-rTsASP2 serum and siRNA. Furthermore, cell monolayer damage due to larval invasion was obviously alleviated when siRNA-treated larvae were used. The adult worm burden, length of adult worms and female fecundity were clearly reduced in mice challenged using siRNA-treated ML relative to the PBS group. Conclusions rTsASP2 possesses the enzymatic activity of native aspartic protease and facilitates T. spiralis invasion of host IECs.